Coffee Supply Chain Management: A Case Study In Ciamis, West Java, Indonesia - Mauladi, Mochamad Arief Rizki; Jangkung Handoyo Mulyo; Dwidjono Hadi Darwanto (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2022)
Ciamis Regency is a potentially developed coffee-producing area in West Java with Arabica and Robusta coffee types. However, in the current marketing process, it is still faced with various obstacles that make the supply chain flow non-optimal. Therefore, in optimizing the Ciamis coffee supply chain management, it is necessary to conduct further research related to supply chain flow, performance, and farmer’s share. This study aims to determine the flow, performance, and farmer’s share of the coffee supply chain in Ciamis Regency. This research uses the descriptive, SCOR, and farmer’s share methods. The results showed that the supply chain flow consisted of material flow in the form of green beans that flowed from upstream to downstream, the flow of information in the form of information (quantity, price, and quality of green beans) that flowed from upstream to downstream and from downstream to upstream, and financial flows in the form of cash payment transactions that flow from downstream to upstream. The performance of coffee supply chain management in Ciamis Regency has an average category with a value of 56.91. The most significant farmer's share value is found in the distribution channel from farmers to inter-regency traders, ending with outside-regency traders.